2014
DOI: 10.3378/027.086.0201
|View full text |Cite
|
Sign up to set email alerts
|

Human Diversity in Jordan: PolymorphicAluInsertions in General Jordanian and Bedouin Groups

Abstract: Abstract. Jordan, located in the Levant region, is a crucial area to investigate human migration between Africa and Eurasia. Even thought, the genetic history of and their apparent selective neutrality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Moreover, in the European and Mediterranean context, these regions of epidemiological importance exhibit the same genetic variation pattern described using sets of neutral markers (e.g. Alu insertion polymorphisms) and genome-wide arrays in previous population studies [ 39 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, in the European and Mediterranean context, these regions of epidemiological importance exhibit the same genetic variation pattern described using sets of neutral markers (e.g. Alu insertion polymorphisms) and genome-wide arrays in previous population studies [ 39 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 61%
“…The number of genetic studies from Jordan increased within the last two decades. This could be due to increased research capacity; the prevalence of different genetic diseases, which were reported to be high among Jordanians as a result of consanguinity and high birth rate; [15][16][17] and having a diverse population that contains many ethnic groups and minorities, 18,19 along with the significant jumps in the census due to waves of immigration toward Jordanian territories from surrounding high tension countries. This increase in the number of genetic studies in Jordan should have been accompanied with an increase in awareness of the importance of applying ethical obligations and morals in the research process including proper informed consent process.…”
Section: Discussionmentioning
confidence: 99%